Impact of the Amlib Integrated Library Management System on Information Management Practices at Egerton University Library, Njoro Campus, Kenya - Nyamboga, Constantine Matoke; Ongus, Raymond Wafula; Njuguna, Andrew Kimanga (Journal of Information and Knowledge, 2013)
The rapid implementation of information technology in all spheres of life, including libraries and information centres, has led to concerns about the paradigm shift in these institutions. This is a case study conducted at Egerton University Library's campus at Njoro, Kenya. A total of fifty three (53) library staff and eight hundred and eighty nine (889) clients constituted the sample size. The sampled library users were stratified as follows: 384 students, 187 academic staff and 318 non-academic i.e. non-teaching staff, respectively. The ensuing data was collected, analyzed and presented using descriptive statistics, in accordance with the objectives formulated. The study focused on the positive changes and subsequent challenges brought about by the introduction and implementation of AMLIB Integrated Library Management System (ILMS) on information management practices in the academic library. Other aspects considered were the involvement staff and patrons in implementation of the system, staff training and attitudes of staff towards the system. Also explained is the influence that the automated system was observed to have, both on staff and patrons, in their day to day transactions. Results show that the system had a significantly greater impact on the overall library operations and on the library's improved image, thereby endearing it to its clients.